PSOOptimizedFast Segmentation Algorithm for 3D Otsu Forest Canopy Image - ZHU Liang-kuan; SHAO Si-xie; JING Wei-peng; LIU Liang (Journal of Harbin University of Science and Technology)
Forest canopy image segmentation is a key step to forest canopy parameters using digital image processing methods According to the characteristics of forest canopy fisheye images with complex background and high resolution, this paper proposed a PSOoptimized forest canopy image decomposition Otsu method 3D segmentation algorithm In this method, the 3D OTSU was decomposed, which reduced the computing time and storage space, and the PSO algorithm was adopted to optimize the twodimensional Otsu to obtain the threshold process Experimental results showed that the algorithm proposed in this paper can quickly and accurately segment the fisheye images of forest canopy, especially in the details of treetops The proposed method can provide a technical support for forest canopy parameters measurement